PERAN GURU DALAM MENGEMBANGKAN KARAKTER ISLAMI PADA KELOMPOK BERMAIN QURROTA A’YUN DI MASA PANDEMI - Desi Pratiwi; Ihda A’yunil Khotimah (STPI Bina Insan Mulia Yogyakarta, 2021)
This research talks about the process of learning Islamic characters during the Covid-19 pandemic, which forced schools to change their learning strategies to switch to using online. This condition makes parents (as teacher partners) find it difficult to provide guidance and assistance to students. The object of research is in KB Qurrota A'yun Sleman Yogyakarta. This research is a qualitative descriptive study with the research subjects of four teachers and six parents of students. The data collection methods are observation, interview, and documentation. The validity of the data used triangulation to check the results of observations and interviews. The results show that the role of the teacher acts as a motivator for parents in providing direction to children so that they are enthusiastic about collecting assignments that are online. While the development of Islamic character that is carried out is (1) in the realm of worship (congregational prayer, reciting, memorizing short letters, memorizing 10 Asmaul Husna) (2) and in the realm of behavior (speaking politely, honestly, answering greetings and saying greetings)